Analaysis of The Effect of Relative Humidity in The Eggs Incubator - Mohd. Isa T. Ibrahim; Ahmad Syuhada; . Hamdani (Syiah Kuala University, 2012)
This study aimed to verify the effect of relative humidity during incubation ofduck eggs in the incubator on the rate of decline in egg weight, hatching day old duck weight, length and hatching eggs energy difference duck. Duck eggs taken from the poultry business in Meunasah Krueng, water fence, Lambaro, Aceh Besar. Then each egg was placed in an incubator unit in the three experimental groups, namely low humidity (57/58% RH), intermediate humidity (67/68% RH) and high humidity (71/72% RH). Incubation process done manually with temperature 38 oC incubator. Eggs were coded X and O adjacent to facilitate marking a reversal in current twice a day. Primary data retrieval from the first day until the fifteenth day by weighing the eggs and using electronic scales. Changes in egg weight reduction on the fifteenth day following (10.666%), (3.853%) and (2.859%) for the treatment of low humidity, intermediate andhigh, then the day of hatching eggs weigh hatching day old duck also showed that the weight is also affected by incubation and humidity differences by ANOVA analysis it can be concluded that the changes in egg weight reduction greatly influence the hatching duck weight difference and the difference so long incubation energy hatching day old duckling have more energy at low humidity (57/58% RH).